HUBUNGAN KEAGENAN PEMERINTAHAN DAERAH DALAM KONTEKS ANGGARAN: SEBUAH AGENDA REKONSTRUKSI - Ratna Ayu Damayanti (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The objectives of this study seem to analyze the agency relationship between executive and legislative in Jembrana local government in budgeting context during the three periods (e.g. new era, reform era, and euphoria reform era), and adat local village in Bali. This study also analyzes the instrument used by the adat local village in reducing conflict of interest and agency loss. Based on the information in adat Bali local village, the study aims at constructing a concept of agency to accommodate the agency relationship in the local government which is suitable for its organization. The method to approach to the study considers the Derrida Model to emphasize the wisdom of local culture values, or also the other isolated models. The paradigm accepts, compares, or synergizes all thoughts, and therefore, neither of definitions, texts nor ideologies appears established. All of these grow like the flowing water to follow the batch or the event flow in the field. It means that the character of the approach does not have absolute structure, form, and formality. The study, hence, utilizes ethnography as a strategy to explore and to map the local value wisdom. The conclusions of this study are: capitalism will be the artificial field where the market must replace the life. The breathing human community becomes merely an object, not subject. The study, then, looks for other alternative outside this consideration by promoting the local wisdom. Such effort really contributes to the construction of yadnya (sincere, balanced) agency relationship pattern and of compensation forms, like olihan-olihan, in which the citizen determines the proportion accepted by the agent.